GENDER-BASED STRATEGIES IN EXPRESSING GRATITUDE IN ENGLISH REALIZED BY INDONESIAN EFL LEARNERS - Lulu Safira Nisa (Department of Master of Linguistic, Universitas Airlangga, 2021)
The goal of this study is to depict the gratitude strategies utilized by Indonesian EFL female and male students in responding to various academic situations. The data were gathered from 85 undergraduate students of English Literature, Faculty of Cultural Studies, Brawijaya University in Malang using Discourse Completion Tasks (DCT) from O’Keeffe, Clancy, & Adolphs (2011). The results show the diversity of gratitude strategies based on Chen, Ho, & Yang's (2005) taxonomy and used by the participants from both genders, varied from brief, lengthy, to complex thanking acts. All participants delivered mixed sets of thanking speech acts, explained in the following conditions: a) social status (students and lecturers), b) indebtedness (lending money to students), c) breaking promises (coming late to presentations), d) between friends (attending the proposal seminar) and e) the setting of public area (letting students to enter the elevator first). It is also revealed that both genders were successfully expressed their gratitude in responding to the five academical contexts made by the researcher.